Analysis of the Electric Power Distribution System Service Reliability Index at PLN Lancang Garam - Aslami, Muhammad Mirdasil; Sadrina, Sadrina; Fachri, Muhammad Rizal (Department of Electrical Engineering Education, Faculty of Engineering, State University of Manado, 2024)
The level of electrical energy demand in an area reflects the welfare of that community The greater the use of electrical energy the higher the community s standard of living followed by the public s critical attitude towards everything that happens and influences lives including electricity services Generally a network s reliability level can be seen from the size of the SAIDI and SAIFI values on the PLN state electricity company side The calculation and reliability analysis results of the Lhokseumawe ULP above show that the total SAIFI index value is 2 68 times year The SAIFI Rayon Lhokseumawe reliability index is categorized as reliable because its value does not exceed the standard set by PLN in SPLN 68 2 of 1986 namely 3 2 times year The total value of the SAIDI index is 45 30 hours year The Lhokseumawe Rayon SAIDI reliability index is categorized as unreliable because its value exceeds the standard set by PLN in SPLN 68 2 of 1986 namely 21 hours year There are certainly differences in infrastructure electrical equipment and number of customers in 1986 compared to current years; this has a different influence on electricity reliability values such as SAIDI and SAIFI < p>